Strategi pembelajaran problem based learning pada mata pelajaran pendidikan agama Islam tema zakat di kelas X SMA Muhammadiyah 1 Klaten - Diva Intan Puteri Sukaca; Mohammad Zakki Azani (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This study aims to identify and describe the strategies used by educators in applying the problem-based learning method to class X Islamic religious education at SMA Muhammadiyah 1 Klaten. This research is a descriptive qualitative research. The source of data in this study is the teacher as the class teacher. Data analysis techniques in this study namely, data reduction, data presentation, and drawing conclusions. The validity of the data in this study used two types of triangulation, namely source triangulation and technical triangulation. The results of this study indicate that it can be concluded that the strategy for implementing Problem Based Learning initiated by SMA Muhammadiyah 1 Klaten teachers is good enough because the objectives in the method itself have been well conveyed, namely creating more active students and realizing learning objectives on indicators of success an independent curriculum that demands that students have a more active role in the process of learning and teaching activities while the teacher is a facilitator.